The Effect of Differences in Light Color Filters on Potato (Solanum tuberosum) Shoot Growth - Fitriani, Salma; Khairunnisa, Nabila; Lafairuz, Nisrina Najla; Putri, Savitri Novantira; Syahrani, Najwa; Setiawan, Gilang; Fitriana, Devita; Rahman, Taufik; Suwandi, Tri (-, 2024)
Potato (Solanum tuberosum) is a plant that plays an important role as a source of food and carbohydrates for the world community after maize, wheat, and rice. The lack of sufficient demand for low yields in Indonesia can be caused by many factors, one of which is environmental factors, which greatly affect the process of growing potatoes. They are temperature, duration of irradiation, light intensity, growing media, and humidity. Because the growth and process of photosynthesis in plants can be affected by the light factor, therefore our aim in conducting this research was to determine the effect of different light color filters on potato mass, number of shoots, shoot length, number of roots, and root length. The research method used was a completely randomized design (CRD) using 4 (four) treatments. The treatment that was given was P1 on potato shoots which were given a clear plastic filter cover (control), P2 with a blue plastic filter cover, P3 with a plastic filter cover, and P4 which was green. Each treatment was repeated three times for 2 weeks with observations every 2 days. The parameters observed were potato mass, number of shoots, shoot length, number of roots, and root length. The data is then analyzed descriptively using the average and standard deviation. There are differences in the average mass of potatoes, number of shoots, shoot length, number of roots, and root length given different light color filter treatments. The color filter treatment that gives the best results for all parameters is the blue filter.